INCIDENCE OF VARIOUS REPRODUCTIVE DISORDERS IN COWS OF PARBHANI DISTRICT - AMBORE, M N; TOTEWAD, G D; NAIK, P M; DHOBLE, R L (The Indian Journal of Animal Reproduction, 2023)
The present work was carried out to find out the various reproductive disorders in cows of Parbhanidistrict. The cows were suffering with various reproductive disorders and their Incidence was recorded.In present study post-partum metrits (36.4 7%) was found to be a common reproductive disorder followed by anestrus (22.29%), repeat breeding (21 .48%), cystic ovaries (16.16%) and subestrus (3.59%).
Keywords: Incidence; Reproductive Disorders; Cows; Parbhani district